A colazione con Enoch Powell - Serra, Maurizio (Rivista di studi politici internazionali, 2008)
ABSTRACT - Enoch Powell (1912-1998) was possibly the most controversial personality in the post-war political scene in the UK. A man of uncommon background, high academic standards, intense conviction and exceptional rhetorical skills, he championed some of the most radical views in matters such as immigration, national identity and defence, the issues concerning Northern Ireland, monetary policy etc. He was seen till the end as the foremost and most consequent opponent of the UK’s participation in the European integration both in Parliament and in the public opinion at large. The article outlines the major facets of his action and heritage, ten years after his death, and gives a personal account of a meeting with the late politician RÉSUMÉ - Enoch Powell (1912-1998) a été probablement le personnage le plus controversé de la scène politique anglaise dans l’après-guerre. Issu d’un milieu non-conformiste, servi par une préparation académique de très haut niveau et de remarquables qualités d’orateur, il a soutenu avec une force de conviction sans faille des vues très controversées sur l’immigration, l’identité nationale et la défense, la question de l’Irlande du Nord, la politique monétaire etc. Il est devenu jusqu’à la fin de sa vie le champion de l’opposition parlementaire et populaire à la participation du Royaume-Uni au processus d’intégration communautaire. L’article présente une analyse des principaux aspects de son action et de son héritage, dix ans après sa mort, ainsi que le compte-rendu d’une rencontre personnelle avec un homme politique hors du commun.